Description of the novel KIR3DL3*04802 allele identified in a southern Chinese Han individual. (15th December 2016) - Deng, Z.‐H.; Zhang, G.‐B.; Chen, R.
Abstract : The novel KIR3DL3*04802 allele differs from the closest allele KIR3DL3*04801 by a single synonymous mutation.